The Handbook of bilingual and multilingual education - Wright, Wayne E.; Boun, Sovicheth; García, Ofelia (Malden, MA : Wiley-Blackwell, 2015)
'Represents the first comprehensive reference work that covers bilingual, multilingual, and multicultural educational policies and practices around the world'--
Introduction: voice in multilingual research teamsCurrent debates in researching multilingualism; Researching multilingualism in multilingual teams; Analytic vignettes: introducing researcher and participant voices; Conclusion; References; 9 Intersections of Language Ideology, Power, and Identity; Introduction; Definitions of key terms and constructs; Bilingual education: psycholinguistic findings and principles; Bilingual education in the context of societal power relations; The polynesian context and the history of literacy in french polynesia.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Multilingualism -- Study and teaching -- Handbooks, manuals, etc; Education, Bilingual -- Handbooks, manuals, etc; Multicultural education -- Handbooks, manuals, etc; Bilingualism; Education, Bilingual -- Handbooks, manuals, etc; Multicultural education -- Handbooks, manuals, etc; Multilingualism -- Study and teaching -- Handbooks, manuals, etc; Multilingualism; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Education, Bilingual; Multicultural education; Multilingualism -- Study and teaching; Electronic books; Handbooks and manuals; Electronic books